Emission and performance characteristics of single cylinder gasoline-fueled spark-ignition engine dually fueled with hydrogen - Orpia, Julius C. (2007)
Hydrogen as a fuel promises to better engine performance and creates zero CO and HC emissions. However, its expensive cost and problems on handling, distribution and storage drags its widespread use. This study investigates the use of small amounts of hydrogen added to standard air-fuel mixture of a single cylinder gasoline engine to possibly reduce HC and CO emissions and improve performance. A Cussons P8150 auto test bench engine was used in the study. It was tested at two flow levels of hydrogen injection and evaluated at rich and lean air-fuel ratios, full and part loads, injection point at downstream and upstream of the carburetor throttle plate, varying engine speeds from 25 to 55 rps and spark timing varied from the manufacturer's standard setting of 21 BTDC. Engine performance and emissions indicators such as torque, power, brake specific fuel consumption, HC and CO emissions were evaluated. The results showed hydrogen addition to rich air-gasoline mixture does not yield desirable performance and emission results. With lean mixture, H2 addition improves power, torque and bsfc and the effect is magnified at lesser spark advance than standard timing. Unburned HC and CO emission slightly increase when H2 was added. Performance levels did not vary much with hydrogen injection location but emission levels were better with upstream location.